2007
DOI: 10.1089/pho.2007.2054
|View full text |Cite
|
Sign up to set email alerts
|

Combined FT-Raman and SEM Studies of the Effects of Er:YAG Laser Irradiation on Dentin

Abstract: Er:YAG laser irradiation with 180 mJ could produce chemical changes in proteins, phosphate, and carbonate in dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 30 publications
5
36
1
3
Order By: Relevance
“…Er:YAG laser irradiation is generally considered to produce less thermal damage of organic tissue is lower than irradiation by other lasers 8,9) . However, the results of the present study indicate that Er:YAG laser irradiation causes chemical changes to the dentin surface [25][26][27] , and that the dentin surface is denatured. The denatured dentin surface typically exhibited a scaly surface and the collagen fibrils were melted.…”
Section: Discussioncontrasting
confidence: 63%
“…Er:YAG laser irradiation is generally considered to produce less thermal damage of organic tissue is lower than irradiation by other lasers 8,9) . However, the results of the present study indicate that Er:YAG laser irradiation causes chemical changes to the dentin surface [25][26][27] , and that the dentin surface is denatured. The denatured dentin surface typically exhibited a scaly surface and the collagen fibrils were melted.…”
Section: Discussioncontrasting
confidence: 63%
“…3C and 4C). An affected layer was described by Soares et al, 10 who noticed it after using the same energy density used in this study. Therefore, organic components, such as collagen fibers, could also be eliminated by NaOCl treatment.…”
Section: Discussionsupporting
confidence: 61%
“…At present, the effect of Er:YAG laser on organic components, such as collagen fibers, remains unclear. Nevertheless, Soares et al 10 have shown, using spectroscopy, that the laser treatment affected the organic substance. Furthermore, Ceballos et al 24 have shown a 3-5 lm thick laser-modified layer, an alteration of the dentin subsurface, beneath which collagen fibrils appear to have lost crossbanding and are fused together, thereby eliminating interfibrillar spaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was sliced in a disc form with 4 mm of thickness and had been already characterized in a previous study [22]. The in vivo setup was tested on human skin of two voluntary students.…”
Section: Methodsmentioning
confidence: 99%